Caffeine levels and dietary intake in smokers with schizophrenia and bipolar disorder. (January 2023) - Rosen, Rachel L.; Ramasubramani, Rahul S.; Benowitz, Neal L.; Gandhi, Kunal K.; Williams, Jill M.
Highlights: · Caffeine intake is high among adult smokers with serious mental illness. · Highest caffeine intake was observed in adults with bipolar disorder. · Self-report caffeine intake was weakly correlated with serum caffeine levels. Abstract: Caffeine is one of the most widely used psychoactive drugs in the United States. High rates of caffeine use have been observed in adult smokers as well as those with serious mental illness. The current secondary analysis aimed to extend previous findings demonstrating high caffeine intake in schizophrenia by examining dietary intake of caffeine and serum caffeine levels in outpatient smokers with schizophrenia (SCZ), bipolar disorder (BP) and control smokers with no psychiatric diagnoses (CON). Two hundred forty-eight adult smokers (SCZ=80; BP=80; CON=88) were included in the current study. Adult smokers with schizophrenia, bipolar disorder, and no psychiatric diagnoses were 40.85 (SD = 11.90) years old on average and all participants were current smokers (∼20 cigarettes per day). Twenty-four hour self-reported caffeine intake (in mg) was highest among individuals with bipolar disorder (median=195.3), followed by adults with schizophrenia (median=155.0) and controls (median=131.7). Participants with bipolar disorder also had the highest serum caffeine levels (in ng/ml; median=1725), followed by those with schizophrenia (median=1194) and controls (median=613.2).  These results provide additional evidence of high caffeine intake among adults with schizophrenia and extend findings by identifying even higher rates of caffeine use in those with bipolar disorder. The current study suggests that caffeine intake is higher among subgroups of patients with serious mental illness.